DEMOCRATIC-PARTICIPATORY LEADERSHIP OF FEMALE PRINCIPALS IN IMPROVING THE QUALITY OF VOCATIONAL HIGH SCHOOLS: A STUDY OF PUBLIC VOCATIONAL HIGH SCHOOLS IN TULANG BAWANG REGENCY - Ari Setioko; Meiliana Bustari (SOSIOEDUKASI, 2026)
This study investigates the implementation of democratic-participatory leadership by female principals in improving the quality of vocational secondary education in Tulang Bawang Regency, Lampung Province, Indonesia. Employing a qualitative multi-site case study design, the research was conducted at two public vocational high schools led by female principals: SMK Negeri 1 Penawar Tama and SMK Negeri 1 Banjar Margo. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving principals, vice principals, teachers, administrative staff, and school stakeholders. The findings indicate that democratic-participatory leadership is characterized by inclusive decision-making, open communication, collaborative problem-solving, and stakeholder involvement in school governance. Leadership effectiveness is strengthened by interpersonal trust, professional collaboration, and organizational support, while challenges arise from uneven teacher participation, disciplinary issues, administrative demands, and gender-related expectations. The study further reveals that participatory leadership contributes to teacher professionalism, organizational cohesion, stakeholder engagement, and the effectiveness of school improvement initiatives. The findings suggest that female principals enhance educational quality by transforming participation into a strategic resource that strengthens collective responsibility, organizational adaptability, and sustainable institutional development within vocational education settings.